Analysis of the pit geometry influence on the rupture by corrosion-fatigue in Zr55Al10Cu30Ni5 bulk metallic glass exposed to distilled water medium - Benjamin GUENNEC (The Japan Society of Mechanical Engineers, 2021)
In a previous work, fatigue experiments performed on Zr55Al10Cu30Ni5 (at.%) bulk metallic glass immersed in distilled water environment have highlighted a causal connection between the generation of corrosion pits and the nucleation of fatigue cracks for the first time in amorphous metallic material. In line with the widely reported results from conventional crystalline materials, additional analyses have suggested an influence of the pit geometry on the occurrence of the fatigue crack nucleation event. Nevertheless, several aspects related to the pit-to-crack transition of the investigated material remain unknown. In the present work, a supplementary investigation based on artificially pitted specimens is undertaken to clarify the effect of the pit aspect ratio on the fatigue behavior of Zr55Al10Cu30Ni5 BMG to assess if the crack nucleation is impacted by the pit geometry. Furthermore, an estimation of the pit geometry effect on the finite fatigue life is also carried out. As an additional involvement, the reason of the slight discrepancy of the fatigue strengths from artificially pitted and smooth specimens is discussed. Experimental results show that the corrosion pit depth governs the fatigue crack nucleation occurrence through the existence of a critical pit geometry, assessed via its aspect ratio in the present work. However, in a noticeable discrepancy with its crystalline counterparts, the influence of the pit geometry on the finite fatigue life of Zr55Al10Cu30Ni5 bulk metallic glass is limited.